Strong Female Character inside Folklore “Camming Puleng” - Muliadi, Muliadi; Amin, Kasma F.; Majid, Abd. (Budapest International Research and Critics University, 2021)
Camming Pulengis the name of a character in folklore, entitled Camming Puleng. Folklore is an oral story told by the narrator to the listener. In this way, folklore can be spread widely in the community. However, nowadays folklore has been widely recorded or published to be preserved so that it does not become extinct. This study aims to describe the values of local wisdom in the Camming Puleng story with a qualitative descriptive method with an ethnopragmatic approach. Ethnopragmatics is a point of view that can be used to understand folklore in the frame of ethnic insight. The results of the analysis show that the female character in Camming Puleng presents two sides of human character values that are different from each other, namely the value of the character of patience (asabbarakeng) and the value of the character of cunning (pabbelleng). The two sides of character values need to be known by readers because they can be one of the determinants in the success of social life in the world and provision of the hereafter.